2005
DOI: 10.1001/archinte.165.1.75
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Interleukin 6 Haplotype Clades With Mortality in Critically Ill Adults

Abstract: The C/C/G, G/G/G, and G/C/C haplotype clades of IL-6 were strongly associated with increased mortality and more organ dysfunction in a cohort of critically ill patients who had SIRS. Haplotype-based analysis succeeded in identifying this association, whereas individual single nucleotide polymorphism-based analysis failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 43 publications
6
62
1
2
Order By: Relevance
“…Although it has been speculated that there may be a potential glucocorticoid receptor at position Ϫ557 to Ϫ552, the sequence around the Ϫ572 site does not have a strong homology to any known transcriptional factor binding site. Thus, these observations, together with the wealth of IL-6 Ϫ174 genotype-association studies (45)(46)(47)(48)(49)(50), indicate that, in Northern Europeans, the IL-6 Ϫ174 genotype is probably the main promoter polymorphism determining variation in IL-6 induction.…”
Section: Discussionmentioning
confidence: 89%
“…Although it has been speculated that there may be a potential glucocorticoid receptor at position Ϫ557 to Ϫ552, the sequence around the Ϫ572 site does not have a strong homology to any known transcriptional factor binding site. Thus, these observations, together with the wealth of IL-6 Ϫ174 genotype-association studies (45)(46)(47)(48)(49)(50), indicate that, in Northern Europeans, the IL-6 Ϫ174 genotype is probably the main promoter polymorphism determining variation in IL-6 induction.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, it was suggested that IL-6-haplotypes, which could be determined by three polymorphisms at position À172, 1753 and 2954 of the IL-6-gene, are better predictors of mortality in critical ill adults than the IL-6-174 genotype alone. 9 However, only 228 patients participated in this study and the results have not been confirmed so far.…”
mentioning
confidence: 82%
“…One such group of haplotypes consists of polymorphisms at the -174 (G/C), +1753 (C/G), and +2954 (G/C) nucleotide positions. In a cohort of critically ill adult patients with SIRS, while no association between each of the SNPs individually and worse clinical outcomes is observed, individuals with the C/C/G, G/G/G or G/C/C haplotype demonstrate a higher mortality and more organ dysfunction [142]. In addition to suggesting that genetic variations within the IL-6 gene influence the severity of sepsis, these observations support the concept that in some instances haplotype analysis may be more valuable in identifying genetic associations compared with individual SNP analysis.…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 89%
“…The association with lower mortality is independent of age and APACHE II score at admission [265]. The association with reduced mortality may be related to the increased fibrinogen A2 allele associated with variable levels of IL-1RA; A2 associated with increased risk of in adults but not children with sepsis; A2 associated with increased mortality in adults with sepsis; +2018 "2 allele" associated with increased mortality in children with meningococcal disease and more severe lung disease in children with pneumonia [120,122,[125][126][127][128] IL-6 -174 G/C G associated with increased IL-6 levels in adult patients but decreased levels in neonates; C associated with increased levels in monocytes from neonates, sepsis in neonates, and severe sepsis and organ dysfunction in children [130,[142][143][144][145][146]281] levels among patients with the GAA haplotype since the 455 A allele within the haplotype is associated with increased transcription. Another polymorphism in the fibrinogen gene, the Val34Leu polymorphism is known to alter the fibrin meshwork with variable permeation characteristics.…”
Section: Fibrinogenmentioning
confidence: 99%